Analisis Kesiapan Guru dalam Melaksanakan Sistem Pembelajaran Kurikulum Merdeka di SD Negeri Timbulharjo Sewon Bantul Yogyakarta - Amanda, Vellia Amanda Putri; Andini, Dinar Westri; Muanifah , Mahmudah Titi (Indonesian Journal of Learning and Educational Studies, 2023)
Readiness is necessary for all professions, especially for teachers. Teachers are one of the determining factors for success in learning activities. The descriptive research aims to describe the readiness of teachers in implementing the independent curriculum learning system at SD Negeri Timbulharjo Sewon Bantul, Yogyakarta. This research is a descriptive qualitative research using purposive sampling subject selection techniques. The subjects in this study were the principal, grade I and IV teachers, and four learners. The results showed that the readiness of teachers in implementing the independent curriculum learning system at SD Negeri Timbulharjo Timbulharjo showed that teachers were ready to implement the independent curriculum. This can be seen from two aspects, namely ability and will.   In the ability aspect, teachers attend various trainings organized by the education office such as training training conducted by Korwil and KKG training. In the learning system, teachers prepare learning tools needed during the learning process. Analyze learning outcomes (CP), conduct diagnostic assessments, develop teaching modules, conduct formative and summative assessments, and evaluate learning and form teams for P5 implementation activities. While in the aspect of willingness, namely in making changes, it is necessary to have psychological maturity of teachers, in this case teachers at SD Negeri Timbulharjo show an attitude of responsibility, confidence, and commitment.